2008
DOI: 10.1542/peds.2007-0930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Buccal Midazolam With Rectal Diazepam in the Treatment of Prolonged Seizures in Ugandan Children: A Randomized Clinical Trial

Abstract: Buccal midazolam was as safe as and more effective than rectal diazepam for the treatment of seizures in Ugandan children, although benefits were limited to children without malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
130
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 30 publications
5
130
1
8
Order By: Relevance
“…[2][3][4] Our results are comparable to those reported in the literature assessing the use of midazolam for seizure control in the emergency setting and reporting success rates of 56 to 96.7%. 3,5,8,10,11,[13][14][15][16][17] To our knowledge, there are no studies comparing IV midazolam to either lorazepam or diazepam IV in the ED setting. Silbergleit and colleagues published a double-blind, randomized, noninferiority trial comparing the efficacy of IM midazolam to that of IV lorazepam: IM midazolam was at least as safe and effective as IV lorazepam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Our results are comparable to those reported in the literature assessing the use of midazolam for seizure control in the emergency setting and reporting success rates of 56 to 96.7%. 3,5,8,10,11,[13][14][15][16][17] To our knowledge, there are no studies comparing IV midazolam to either lorazepam or diazepam IV in the ED setting. Silbergleit and colleagues published a double-blind, randomized, noninferiority trial comparing the efficacy of IM midazolam to that of IV lorazepam: IM midazolam was at least as safe and effective as IV lorazepam.…”
Section: Discussionmentioning
confidence: 99%
“…12 Multiple studies have proven that midazolam is at least as effective as diazepam in terms of safety and risk of recurrence, with the advantage of providing a faster initiation of treatment, leading to more rapid seizure cessation. 3,5,8,10,11,[13][14][15][16][17][18][19] Midazolam has emerged as a highly efficacious drug in the treatment of impending SE, with several routes of administration exhibiting high bioavailability. 19 In a recent article proposing evidence-based and expert consensus practice guidelines, the Neurocritical Care Society lists midazolam as Class I, Level A for the emergent treatment of SE, as Class IIB, Level B for urgent treatment (continuous infusion), and as Class IIa, Level B for refractory treatment using the evidence rating system of the American Heart Association. )…”
mentioning
confidence: 99%
“…60,61 Comparatively, buccal midazolam also resulted in a greater reduction in the likelihood of seizure recurrence 1 hour after administration, with no difference in respiratory arrest or depression.…”
Section: Therapy: IV Vs Non-iv Treatmentmentioning
confidence: 93%
“…13,51,53,55,58,59 In general, investigators have shown that while benzodiazepines delivered via an IV have a more rapid onset of action from dose delivery to seizure cessation, a greater amount of time is required to place the IV than to deliver the therapy by non-IV routes. 13,55,59,60,61 Therefore, the total amount of time from the decision to treat with a benzodiazepine to seizure cessation is equivalent or less when alternative routes are used. Specifically, this has been shown for midazolam when delivered by the IM, IN, or buccal routes.…”
Section: Therapy: IV Vs Non-iv Treatmentmentioning
confidence: 99%
See 1 more Smart Citation